Embodied Carbon in Buildings Measurement, Management, and Mitigation - Pomponi, Francesco; De Wolf, Catherine; Moncaster, Alice; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book provides a single-source reference for whole life embodied impacts of buildings. The comprehensive and persuasive text, written by over 50 invited experts from across the world,  offers an indispensable resource both to newcomers and to established practitioners in the field. Ultimately it provides a persuasive argument as to why embodied impacts are an essential aspect of sustainable built environments. The book is divided into four sections: measurement, including a strong emphasis on uncertainty analysis, as well as offering practical case studies of individual buildings and a comparison of materials; management, focusing in particular on the perspective of designers and contractors; mitigation, which identifies some specific design strategies as well as challenges; and finally global approaches, six chapters which describe in authoritative detail the ways in which the different regions of the world are tackling the issue. Provides a comprehensive, up-to-date guide to embodied carbon calculation and reduction, with a particular focus on understanding uncertainty; Includes examples of approaches used by industry professionals, and specific routes to embodied carbon reduction; Identifies the methodologies, tools and standards in use around the world.
Part I - Measurement.- Uncertainty Analysis in Embodied Carbon Assessments: What Are the Implications of its Omission?.- Probabilistic approaches to the measurement of embodied carbon in buildings.- Uncertainty Assessment of Comparative Design Stage Embodied Carbon Assessments.- Embodied Carbon of Wood and Reinforced Concrete Structures Under Chronic and Acute Hazards.- Embodied Carbon of Surfaces: Inclusion of Surface Albedo Accounting in Life Cycle Assessment.- Quantifying Environmental Impacts of Structural Material Choices Using Life Cycle Assessment: A Case Study.- Analysis of Embodied Carbon in Buildings Supported by a Data Validation System.- Part II - Management.- Embodied Carbon Tools for Architects and Clients Early in The Design Process.- Embodied Carbon Research and Practice: Different Ends and Means or a Third Way.- Embodied Carbon in Construction, Maintenance and Demolition in Buildings.- Carbon and Cost Hotspots:  An Embodied Carbon Management Approach During Early Stages of Design -- Part III - Mitigation.- Applying circular economic principles to reduce embodied carbon.- Embodied Carbon of Sustainable Technologies.- Accounting for Embodied Carbon Emissions in Planning and Optimisation of Transport Activities During Construction.- Design Strategies for Low Embodied Carbon in Building Materials.- Embodied Carbon of Tall Buildings: Specific Challenges -- Part IV - Approaches Across Global Regions.- Managing Embodied Carbon in Africa Through a Carbon Trading Scheme.- Embodied carbon in buildings: an Australian perspective.- Current approaches for embodied carbon assessment of buildings in China: An overview.- Embodied carbon measurement, mitigation and management within Europe, drawing on a cross-case analysis of 60 building case studies.- Initiatives to Report and Reduce Embodied Carbon in Buildings in North America.- Embodied and Life Cycle Carbon Assessment of Buildings in Latin America - State-of-the-art and Future Directions -- Index.
Keywords: Buildings -- Design and construction; Energy policy; Energy and state; Renewable energy sources; Building Construction and Design; Energy Policy, Economics and Management; Renewable Energy